Fifth Grade Safari - Jeff Mangiat (U.S.A, 1993)
When Mrs. Wilmont's fifth grade class visits a big city zoo, they discover that the long-standing feud between the Wacky Facts Lunch Bunch and their rivals, the Nasty Blobs, does not stop at the zoo gates
Keywords: Realistic Fiction -- Realistic Fiction